Management of Hazardous Wastes - El-Din Saleh, Hosam M.; Abdel Rahman, Rehab O. (IntechOpen, 2016)
Rapid trend of industry and high technological progress are the main sources of the accumulation of hazardous wastes. Recently, nuclear applications have been rapidly developed, and several nuclear power plants have been started to work throughout the world. The potential impact of released hazardous contaminants into the environment has received growing attention due to its serious problems to the biological systems. The book Management of Hazardous Wastes contains eight chapters covering two main topics of hazardous waste management and microbial bioremediation. This book will be useful to many scientists, researchers, and students in the scope of development in waste management program including sources of hazardous waste, government policies on waste generation, and treatment with particular emphasis on bioremediation technology.